Investigação da força de relações em classes de equivalência sob emparelhamento com o modelo atrasado (DMTS) - Ribeiro, Giovan Willian (2018)
Delayed matching to sample (DMTS) enhances the formation of equivalence classes and the transfer of functions between equivalent stimuli when compared to the simultaneous matching to sample (SMTS). A classes reorganization procedure permits to assess how much previous established relations are susceptible to modifications, therefore allowing to verify if DMTS training results in equivalent stimuli more strongly related to each other when compared to SMTS training. The present study explored this alternative. Experiment 1 aimed to evaluate the effects of conditional discrimination reversals, accomplished by DMTS or SMTS trainings, on the reorganization of equivalence classes established by a DMTS training. Undergraduate students were submitted to a DMTS procedure (2s) to learn AB, AC, and AD relations. After emergence of B1C1, B2C2, C1B1, C2B2, B1D1, B2D2, D1B1, D2B2, C1D1, C2D2, D1C1 and D2C2 relations, participants were divided into two groups for the remaining stages of the experiment: DMTS Group continued with DMTS (2s), while the SMTS Group was exposed to the SMTS. A reversal training modified AD relations (A1D2, A2D1) and classes reorganization tests verified whether the modifications altered the baseline equivalence relations. Out of 20 participants, 15 reorganized the classes. There were no significant differences between the groups. The high percentage of reorganization suggests that this process is independent of the presence or absence of the delay. The reversal of AD relations provoked a transient reversal of the other baseline relationships, affecting the classes as a whole. However, it is still unclear how DMTS favors class formation and function transfer, as observed in previous studies. It is possible that participants submitted to DMTS engage in precurrent behaviors during the sample-comparison delay, establishing a responses chain not planned by the scheduled contingencies. The objective of Experiment 2 was to verify if operant responses explicitly required during the DMTS interval (and verbal stimuli related to them) could become members of equivalence classes, which could be an additional source of stimulus control that partially accounts for the observed effects under this procedure. Undergraduate students performed a training of AB (A1B1, A2B2) and AC (A1C1, A2C2) relations with a DMTS (2s). At each AC training trial, a different mathematical task was presented during the DMTS delay and the participant was instructed to verbalize its result. When A1 was the sample stimulus the result of the task was always 12, and when A2 was the sample the result was always 9. Along with BC and CB trials, equivalence tests included trials in which printed numbers 12 (R1) and 9 (R2) were presented either as sample stimuli (RB, RC) or as comparison stimuli (BR, CR) in order to verify if responses emitted during the DMTS delay would be included in the classes. Additionally, relations between the words EVEN (P1) and ODD (P2) and the stimuli of sets B and C were tested. Performance of ten out of eleven participants showed formation of the equivalence classes A1B1C1R1P1 and A2B2C2R2P2. All participants attributed the stimuli P1 and P2 to the same classes as R1 and R2. These findings confirmed that precurrent responses may become members of equivalence classes and suggest that this is one of the possibilities to explain the effects of DMTS in other studies.